2018
DOI: 10.1021/acs.estlett.8b00084
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Oxidation of Oil Reduced the Effectiveness of Aerial Dispersants Applied in Response to the Deepwater Horizon Spill

Abstract: Chemical dispersants are one of many tools used to mitigate the overall environmental impact of oil spills. In principle, dispersants break up floating oil into small droplets that disperse into the water column where they are subject to multiple fate and transport processes. The effectiveness of dispersants typically decreases as oil weathers in the environment. This decrease in effectiveness is often attributed to evaporation and emulsification, with the contribution of photochemical weathering assumed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 12 publications
(34 reference statements)
7
61
0
Order By: Relevance
“…However, its influence on the changes in the physical properties of Heidrun was limited, since solar radiation decreased over the length of the experiments conducted in both seasons. The results for Heidrun are substantiated by the work of others, where photo-chemical weathering had a major influence on the rates of changes in the physical properties of a conventional crude oil spilled in water [10].…”
Section: Multiple Correlation Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…However, its influence on the changes in the physical properties of Heidrun was limited, since solar radiation decreased over the length of the experiments conducted in both seasons. The results for Heidrun are substantiated by the work of others, where photo-chemical weathering had a major influence on the rates of changes in the physical properties of a conventional crude oil spilled in water [10].…”
Section: Multiple Correlation Analysissupporting
confidence: 56%
“…The warmer air temperature in summer caused evaporation of volatile chemicals (<C10), resulting in thicker more viscous oil slicks. A recent lab study [10] reported that both evaporation and photo-chemical oxidation result in increases in the density and viscosity of oil, but the increases were predominately higher for oil exposed to solar radiation. However, AWB contains condensate as the diluent, a liquid product of natural gas extraction.…”
Section: Multiple Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, δ 18 O is a novel approach to track the oxidative fate of hydrocarbons released to aquatic systems, which may improve our capacity to respond effectively to future accidents (Ward, Armstrong, et al, 2018). In addition to improved sensitivity, δ 18 O may provide a means to disentangle the relative importance of pathways that can simultaneously weather hydrocarbons in surface waters, such as evaporation, photochemical oxidation, and biological oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the kinetic isotopic fractionation of dissolved O 2 photochemically incorporated into hydrocarbons ( 18 ε oxidation = −9‰) appears to be independent of OC physical and chemical properties, raising the possibility that a variety of OC types (e.g., crude oil and DOC) share a common step in the photochemical oxidation mechanism. Collectively, δ 18 O is a novel approach to track the oxidative fate of hydrocarbons released to aquatic systems, which may improve our capacity to respond effectively to future accidents (Ward, Armstrong, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%